Development of a Photothermal Deflection Analyzer for Measurement of Thermophysical and Thermo-Optical Properties of Fluids - Kuan, Ya Chin (2008)
Photothermal deflection techniques are non-contact methods for optical and thermal properties characterization of solids, liquids and gases. The main focus in this project was to design, construct and test reliability of an instrument based on the principle of photothermal deflection technique. In this technique, the heating source is a NiCr resistance wire and the probe beam is a CW HeNe. The instrument is intended for the characterization of thermal properties of liquids and it is named Photothermal Deflection Analyzer (PTDA). The PTDA setup consists mainly of a CW HeNe probe laser beam, a NiCr resistance wire, a position sensitive detector and a personal computer with an installed data acquisition card. The PTDA measured the deflection of a probe beam passing near a heating source immersed in a liquid sample. The beam deflection is caused by the refractive index gradient induced by the temperature change in the liquid. The deflection angle of the probe laser beam is measured by the position sensitive detector. Short electrical pulses from a data acquisition card generated across the resistance wire cause a heating gradient in the liquid. The duration and temporal shape of the electrical pulses can be change in a wide range. The temperature distribution of the heating wire and liquid is simulated by solving numerically a coupled transient heat conduction equations for wire and liquid. The effect of different temporal profiles and pulse durations of the heating source to the temperature distribution in the liquid is discussed. Using obtained temperature profile it is possible to calculate the probe beam displacement. Thermal properties of the liquid can be determined by comparing the numerical and experimental probe beam displacement. In order to test the reliability of the PTDA, thermal properties of selected liquid samples: distilled water, alcohol, sodium chloride liquid solution and coconut oil were determined. The thermal properties for distilled water and alcohol show a good agreement with the literature. For sodium chloride liquid solution, the PTDA is sensitive enough to sense the changes of thermal properties due to the variation of the solution concentration. The thermal diffusivity of coconut oil was dependent to the moisture content whereas the thermal conductivity and thermo-optical properties was not affected by the moisture content. Presently to the best of our knowledge, there is no literature data on thermal properties of coconut oil versus moisture content.